A case report of necrotizing enterocolitis in a moderately preterm neonate with LCHADD—A call to focus on the basics while utilizing advanced new therapies - Metzler, Marina; Burns, William; Mitchell, Carly; Napolitano, Stephanie; Chaudhari, Bimal P. (Frontiers in Pediatrics, 2023)
Long chain 3-hydroxyacyl-CoA dehydrogenase deficiency (LCHADD) is an autosomal recessive condition of impaired beta-oxidation. Traditionally, treatment included restriction of dietary long chain fatty acids via a low-fat diet and supplementation of medium chain triglycerides. In 2020, triheptanoin received FDA approval as an alternative source of medium chain fatty acids for individuals with long chain fatty acid oxidation disorders (LC-FAOD). We present a case of a moderately preterm neonate born at 33 2/7 weeks gestational age with LCHADD who received triheptanoin and developed necrotizing enterocolitis (NEC). Prematurity is known as a major risk factor for NEC, with risk increasing with decreasing gestational age. To our knowledge, NEC has not previously been reported in patients with LCHADD or with triheptanoin use. While metabolic formula is part of the standard of care for LC-FAOD in early life, preterm neonates may benefit from more aggressive attempts to use skimmed human milk to minimize exposure to formula during the risk period for NEC during feed advancement. This risk period may be longer in neonates with LC-FAOD compared to otherwise healthy premature neonates.